Phytosanitary products use method in cowpea production in the commune of adjohoun, Benin - HOUNSOU, BIDOSSESSI MATHIEU (My University, 2018)
This study aimed at identifying the chemical pesticides used in cowpea production and their different ways of use in the Adjohoun commune, in the South East of Benin. Thus, 323 farmers have been surveyed and the observations of their agronomic practices have allowed us to collect information on water contamination due to the use of pesticides. The chemical control has been identified as the main method to control the pests. Nevertheless, farmers recognize the effects of the synthetic pesticides use and are informed about the use of essences to control pests. However, few of them use botanical pesticides against pests. But, they are ready to use botanical pesticides if they are available, accessible, effective and cheap, to overcome the effects of chemical pesticides on health and environment. This study showed that various types of chemical pesticides such as COTALM P 218 EC, CYPERCAL 50 EC, Phostoxin etc…were used. The sources of the environmental risks are the parallel pesticides supply channels, the cleansing of the spreading equipment in water sources (about 85% of the farmers do that) and the non-compliance with the technical guidelines of the pesticides use. The risk assessment allowed us to highlight the health-related risks, surface water pollution risks and soils contamination risks. So, best agronomic practices are essential for a sustainable exploitation of the natural resources in this commune.
Keywords: Cowpea; chemical pesticides; risk.